PENGARUH KONSENTRASI KEPEMILIKAN, STRUKTUR MODAL, LIKUIDITAS, DAN PROFITABILITAS TERHADAP RETURN SAHAM - Ines Tasia Agustin; Taswan Taswan (Jurnal Bisnis dan Ekonomi, 2017)
The objective of the study is to examine the effect of Concentration of Ownership (CON), Capital Structure (DER), Liquidity (CR), and Profitability (ROA). This research was conducted using secondary data. Population in this research is a manufacturing company in Indonesia Stock Exchange (IDX) from 2011 up to 2013. Sampling technique used was purposive sampling. There are 172 manufacturing compeanies being analysed. This study uses multiple regression analysis.The research proves that the concentration of ownership (CON)have positive and significant impact on stock return, Capital Structure (DER), Liquidity (CR), and Profitability (ROA) have positive and not significant effect on stock return. Adjusted R Square is 0,045 this means thant 4,5% of the dependent variable can be explained by the independent variable , while the remaining 95,5 % is explained by other causes outside the model Keywords: StockReturn, Concentration of Ownership, Debt to Equity Ratio, Current Ratio, and Return on Asset.